Creative Wear / Halimatul Saadiah Abdul Hamid ... [et al.] - Abdul Hamid, Halimatul Saadiah; Idris, Nurkhazilah; Che Dan, Siti Khadijah; Mohamed Tahir, Norfaezah; Ahmad Sabri, Shazwani (Faculty of Artistic and Creative Technology, 2006)
CreativeWear provides and manufactures: uniform Jacket, t-shirt, track suit, wind breaker, towels, pillow case or bed sheet, badges, caps, jerseys, bags, pouch, batik shirt and scarf, tie and vest according to our customers needs. Almost all our clients are from universities, polytechnics, colleges, primary and secondary schools, government agencies, private firms, clubs and personnel We custom made the products according to the customers desire. In other words, customers can come up with their own special design or leave the creative work to our designers. Then, the designers will send the designs to the respective vendors and there, stitching, sewing, printing and sometimes even painting process will be done. The final product will be delivered to the customers by van or lorry. The interesting part of CreativeWear is that we apply the vendor system. We do not have any machines to make the attires or souvenirs. Instead, we send them to networking vendors who will produce the product. The advantage is that we will never have to consider the maintenance of machines subsequently reducing the number of manpower. We pay our vendors according to the segregation of operations. In the production of designed t-shirt for example, 20% is given to the printing vendor, 10% to our embroidery vendor and 12% for cutting and sewing. All of our employee undergo training and our designers are always updated with the latest design in the market, CreativeWear operates Monday to Friday from 9 am to 5pm and on Saturday morning from 9am to 1pm.